Toxic stress of lead on clarias gariepinus (African catfish) fingerlings (2003)
The toxic stress of lead on fish was tested employing a 96-hour bioassay test. The experimental fish used were Clarias gariepinus fingerlings. Lead in the form of lead chloride was used to prepare the stock solution. The concentrations of lead used for the experiment were 0, 1.8, 3.2, and 5.6, and10.0mg/l. The lethal concentration (LC50) was estimated using the logarithmic method and was found to be 0.6, 0.58 and 0.62mg/l for replicates1, 2 and 3 respectively.